Youth in Elderly Care Sector – Mission Impossible? - Krutulienė, Sandra; Okunevičiūtė, Laima; Gruževskis, Boguslavas (Socialinė teorija, empirija, politika ir praktika, 2022)
The aging of population leads to the outcome that number of social care sector clients grows steadily. Hence the research highlighted that average age of the workforce in social care sector is also rising. An important question is how to attract and retain young people in the care sector for the elderly in the context of an aging society with the growing importance of the care economy. The study aims to reveal the factors motivating young people (18-29 years old) to employ and their attitudes towards work in the elderly care sector to. The research investigated the links between prosocial motivation and the attitudes of unemployed young people registered in the Employment Service toward work in the elderly care sector. The results of the study identified main directions, which could encourage more young people to get involved in the elderly care sector: promoting prosocial motivation of the individuals, increasing the flexibility of social services for the elderly and ensuring good working conditions. The study revealed significant role of the employment service as an intermediary between the young person and the institution providing social services and changing public attitudes towards work in the care sector for the elderly.